Dubious by nature - Tallant, Jonathan (Taylor & Francis, 2013)
There is a charge sometimes made in metaphysics that particular commitments are ‘hypothetical’, ‘dubious’ or ‘suspicious’. There have been two analyses given of what this consists in—due to Crisp (2007) and Cameron (2011). The aim of this paper is to reject both analyses and thereby show that there is no obvious way to press the objection against said commitments that they are ‘dubious’ and objectionable. Later in the paper I consider another account of what it might be to be ‘dubious’, and argue that this too fails. I use Bigelow's (1996) Lucretian properties as a vehicle for the discussions of dubiousness that follow. As a consequence, the paper ends up offering a partial defense of Lucretianism.